2000
DOI: 10.1038/sj.sc.3101052
|View full text |Cite
|
Sign up to set email alerts
|

A histopathological analysis of the human cervical spinal cord in patients with acute traumatic central cord syndrome

Abstract: Study design: We have applied conventional histochemical and morphometric techniques to study the changes within the human spinal`hand' motor neuron pool after spinal cord injury in patients who presented with acute traumatic central cord syndrome (ATCCS). Objective: To determine whether a reduction of large alpha motor neurons at the C7, C8 and T1 spinal cord levels underlies the mechanism which causes hand dysfunction seen in patients with (ATCCS). Background: The etiology of upper extremity weakness in ATCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 14 publications
2
35
0
Order By: Relevance
“…25 Numerous preclinical studies have indicated that immediately after SCI, the disruption of endothelial cells, axons, and the cytoskeleton, in association with molecular cascades and ionic imbalances, results in cytotoxic and vasogenic spinal cord edema, collectively labeled "secondary injury." [11][12][13][17][18][19]26,35,36,43,62,65,67,68 The results of combined MRI and necropsy investigations by Quencer et al, 59 Jimenez et al, 46 and Martin et al 53 of patients who died within a few days after acute traumatic central cord syndrome indicated that axonal swelling and disruption in association with minimal co- agulative necrosis of gray matter are visualized as a highintensity signal IML on T2-weighted MR images. These patients with partial SCI did not show hematomyelia in histological sections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Numerous preclinical studies have indicated that immediately after SCI, the disruption of endothelial cells, axons, and the cytoskeleton, in association with molecular cascades and ionic imbalances, results in cytotoxic and vasogenic spinal cord edema, collectively labeled "secondary injury." [11][12][13][17][18][19]26,35,36,43,62,65,67,68 The results of combined MRI and necropsy investigations by Quencer et al, 59 Jimenez et al, 46 and Martin et al 53 of patients who died within a few days after acute traumatic central cord syndrome indicated that axonal swelling and disruption in association with minimal co- agulative necrosis of gray matter are visualized as a highintensity signal IML on T2-weighted MR images. These patients with partial SCI did not show hematomyelia in histological sections.…”
Section: Discussionmentioning
confidence: 99%
“…These patients have axonal swelling and disruption in conjunction with minimal coagulative necrosis of the spinal cord parenchyma. 1,2,24,26,46,53,59,75 As evident in experimental models of SCI, 20,57,64 IML expansion in humans has yet to be fully validated. 2 At the microscopic level, histopathological studies have shown that IML expansion occurs primarily within the first 24 hours after trauma.…”
mentioning
confidence: 99%
“…Recent neuropathological studies further suggested that the clinical deficits observed in the early phase of CCS are largely due to the loss of large, monosynaptic, rapidly conducting, myelinated corticospinal fibers. 13 Schneider et al 23 suggested that CCS was associated with a fairly good prognosis, because as the spinal cord edema subsided, motor function would recover, following a definite pattern, and thus, surgical intervention was contraindicated. Furthermore, the condition of some of the patients treated with laminectomy deteriorated dramatically after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent past, the historical report of Schneider et al 1 has been challenged. Not only have the original descriptions of pathogenesis and neuroanatomical basis of TCCS been criticized, [7][8][9][10][11] but optimal treatment of the condition has also been reappraised. 3,[12][13][14][15][16] This survey study challenges the ambiguity of the TCCS definition as introduced by Schneider et al Whereas several physicians assign a diagnosis of TCCS in SCI patients with only 1 motor score point lower in the upper extremities than in the lower extremities, other physicians consider patients with a minimum difference of 15 points as TCCS patients.…”
Section: Discussionmentioning
confidence: 99%